The role of (RPA) technology in improving the quality of internal audit (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Technological development in accounting practices is a major trend that has grown significantly over the past years and is more prominent today than ever before. Development has now entered a new phase where automation of accounting processes is seen as a growing concept that will undoubtedly impact the accounting and auditing profession.The research aimed to identify the importance of applying robotic process automation(RPA) technology in Iraqi institutions, especially in the Education Directorate in Thi Qar Governorate, and what effects the application of robotic process automation technology may have on the quality of internal auditing.To achieve the goal of the research, the researchers relied on the descriptive approach and used available modern research and theses, in addition to the field study method using the questionnaire as the main tool for collecting basic data for the research, where the research sample consisted of accountants and auditors of the Education Directorate in Thi Qar Governorate.A set of conclusions were reached, the most important one is: that applying robotic process automation technology has a role in improving the professional practices of accountants and auditors and thus improving the quality of internal auditing, and that the benefits of adopting automated processes outweigh its disadvantages. In light of this, a set of recommendations were proposed, the most important one is that: the necessity of adopting robotic process automation due to its role in increasing efficiency and accuracy and improving the quality of internal auditing.